(untitled) (Journal of Applied Learning and Teaching, 2020)
Thou shalt not lie. Kant famously said one must always tell the truth. Even with a murderer at the door one cannot lie. Probably no one else holds this extreme view. There are times a lie is appropriate, ethical. When might it be permissible to lie? Are there times when it might be not only OK to lie but be appropriate to lie? But others remind us that a business cannot succeed in the long run by lying, In education we help people learn how to make effective and ethical choices. Specific examples and minicases related to these issues help get classroom or online conversations started. Question are discussed, usually in dyads. The discussion does not end here. Our classroom experiences and feedback from students convinces us: to tell the truth, sometimes it pays to lie.